Effects of human interleukins in the transgenic gene reporter cell lines IZ-VDRE and IZ-CYP24 designed to assess the transcriptional activity of vitamin D receptor - Bartonkova, Iveta; Kallay, Enikoe; Dvorak, Zdenek (PloS one, 2018)
The role of vitamin D receptor (VDR) in immune responses has been broadly studied and it has been shown that activated VDR alters the levels of some interleukins (ILs). In this study, we studied the opposite, i.e. whether 13 selected pro-inflammatory and anti-inflammatory ILs influence the transcriptional activity of human VDR. The experimental models of choice were two human stably transfected gene reporter cell lines IZ-VDRE and IZ-CYP24, which were designed to evaluate the transcriptional activity of VDR. The gene reporter assays revealed inhibition of calcitriol-induced luciferase activity by IL-4 and IL-13, when 1 ng/mL of these two compounds decreased the effect of calcitriol down to 60% of the control value. Consistently, calcitriol-induced expression of CYP24A1 mRNA was also significantly decreased by IL-4 and IL-13. The expression of VDR and CYP27B1 mRNAs was not influenced by any of the 13 tested ILs. These data suggest possible cross-talk between the VDR signalling pathway and IL-4- and IL-13-mediated cell signalling.
Keywords: CYP24A1; transfekce; receptory kalcitriolu; transgeny; Cell Line; 25-Hydroxyvitamin D3 1-alpha-Hydroxylase; Interleukins; interleukiny; Transfection; Transcription, Genetic; reportérové geny; genetická transkripce; 1-alfa-hydroxylasa 25-hydroxyvitaminu D3; lidé; Receptors, Calcitriol; Humans; buněčné linie; Vitamin D3 24-Hydroxylase; Transgenes; Genes, Reporter